A novel mutation in FRMD7 causes X-linked idiopathic congenital nystagmus in a North Indian family. (15th June 2015) - Gupta, Shashank; Pathak, Ekta; Chaudhry, Vidya Nair; Chaudhry, Prashaant; Mishra, Rajeev; Chandra, Abhishek; Mukherjee, Ashim; Mutsuddi, Mousumi
Highlights: This is the first genetic investigation of a North Indian family affected with XLICN. We have screened the candidate gene FRMD7 to identify the causal mutation for ICN. A novel causal mutation c.556A > G (p.M186V) was identified in the gene. Protein structural modeling of the normal and mutant FRMD7 protein was performed. The mutation is predicted to disrupt intra-domain interactions in the FERM domain. Abstract: Idiopathic congenital nystagmus (ICN) is the most common form of oculomotor disorder characterized by involuntary bilateral ocular oscillations. Primarily the disease is an ocular anomaly but the pathophysiology is associated with neuronal cytoskeletal dynamics in the brain. In the current study, a three generation North Indian family affected with X-linked idiopathic congenital nystagmus (XLICN) was recruited. Our aim was to identify the causal mutation for ICN in the family by screening the candidate gene, FERM domain containing-7 ( FRMD7 ). This gene has been implicated in XLICN as it regulates neuronal cytoskeletal proteins and neurite outgrowth in the developing brain. Therefore, the entire protein coding region, including splice junctions, 5′ UTR and 3′ UTR of FRMD7 was screened by PCR-Sanger sequencing. Targeted sequencing revealed a novel A to G transition in the exon seven (c.556A > G), resulting in a conservative substitution of methionine by valine at codon 186 (p.M186V). A cohort of healthy individuals was also checked for presence of the putative causal variant by allele specific PCR. All the affected males and carriers in the family shared this variant; however, this was absent in the unaffected males as well as 100 unrelated healthy individuals. Further, protein homology modeling revealed that the change p.M186V might destabilize the interaction between the FERM-M and FERM-C domains. The in silico prediction supports pathogenicity of the mutation; nevertheless it needs in vivo validation in the future. This is the first genetic investigation of XLICN in a North Indian family where we report a novel causal mutation c.556A > G (p.M186V) in the gene FRMD7 .